2004
DOI: 10.1023/b:verc.0000009534.64533.b9
|View full text |Cite
|
Sign up to set email alerts
|

Some Pharmacokinetic Parameters of R-(–)- and S-(+)-Ketoprofen: The Influence of Age and Differing Physiological Status in Dairy Cattle

Abstract: The pharmacokinetic parameters of ketoprofen have previously been studied in cattle, but no studies have been performed on differing ages and metabolic situations in these animals. The aim of this work was to study the possible modifictions of the pharmacokinetics of ketoprofen enantiomers that may result from age, lactation or gestation in dairy cattle. Three groups of Holando Argentino cattle contained, respectively, 8 cows in early lactation, 8 pregnant cows and 8 newborn calves. Four animals from each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
1
24
2
1
Order By: Relevance
“…Further studies are warranted to clarify the metabolism or flurbiprofen and to determine the extent and possibility of stereoselectivity in biliary excretion of the newborn calves. An enantiomeric difference related to age has been found previously following administration of (R)-(−)-and (S)-(+)-ketoprofen; the half life in calves was longer than in cows (Igarza et al, 2004). These results indicate the metabolic differences in the same species between these compounds of similar chemical structure.…”
Section: Discussionmentioning
confidence: 50%
“…Further studies are warranted to clarify the metabolism or flurbiprofen and to determine the extent and possibility of stereoselectivity in biliary excretion of the newborn calves. An enantiomeric difference related to age has been found previously following administration of (R)-(−)-and (S)-(+)-ketoprofen; the half life in calves was longer than in cows (Igarza et al, 2004). These results indicate the metabolic differences in the same species between these compounds of similar chemical structure.…”
Section: Discussionmentioning
confidence: 50%
“…Most papers published on the pharmacokinetics of drugs in pregnancy report clearance and volume parameters calculated using either traditional mammillary compartmental or non-compartmental methods (1)(2)(3). Other pharmacokinetic papers provide descriptive parameters such as area under the curve, half-life, terminal rate constants, concentration maximum (Cmax), time to reach Cmax, and mean residence time (4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…, 2004). Igarza et al. (2004) showed that newborn calves had lower clearance and longer elimination half‐life of ketoprofen compared to adult cows.…”
Section: Introductionmentioning
confidence: 99%